Cities for driverless vehicles : planning the future built environment with shared mobility - Zhang, Xu (ICE Publishing, 2022)
This work outlines the infrastructure requirements needed to prepare for autonomous vehicles. With insights from urban planners across the world, it examines how our future cities will look, what legal requirements will need to be made, how people will interact with driverless cars and lorries, the Mobility as a Service (MaaS) concept and how professionals can plan and prepare for this new technological age.